Quantification of carious pathogens in the interdental microbiota of young caries-free adults - Bourgeois, Denis; David, Alexandra; Inquimbert, Camille; Tramini, Paul; Molinari, Nicolas; Carrouel, Florence (PloS one, 2017)
The majority of caries lesions in adults occur on the proximal tooth surfaces of the posterior teeth. A comprehensive study of the composition of the oral microbiota is fundamental for a better understanding of the etiology of interdental caries. Twenty-five caries-free subjects (20-35 years old) were enrolled in the study. The interdental biofilm of four interdental sites were collected. The real-time polymerase chain reaction (PCR) methodology were used to quantify (i) the following bacteria: Streptococcus spp., Streptococcus mutans, Lactobacillus spp., Enterococcus spp., and Enterococcus faecalis; (ii) the fungus Candida albicans; and (iii) total bacteria. Streptococcus spp. was the most abundant species, followed by Lactobacillus spp. and Enterococcus spp. Streptococcus spp. and Lactobacillus spp. were detected at all tested sites and Enterococcus spp. at 99% of sites. S. mutans was detected at only 28% of the tested sites and C. albicans was detected at 11% of sites. E. faecalis was never detected. In 54.5% of the biofilm inhabited by C. albicans, S. mutans was present. Moreover, 28% of the ID sites co-expressed S. mutans and Lactobacillus spp. The studied pathogens were organized into two correlated groups of species. Strikingly, the fungus C. albicans and the bacteria Enterococcus spp. cluster together, whereas Streptococcus spp., S. mutans and Lactobacillus spp. form one distinct cluster. The interdental biofilm of young caries-free adults is comprised of pathogens that are able to induce interproximal caries. That several of these pathogens are implicated in heart disease or other systemic diseases is an argument for the disruption of interdental biofilms using daily oral hygiene.